Federally qualified health center patients’ experiences with remote patient monitoring as part of telehealth services for self-measured blood pressure monitoring - Natalia I. Heredia; Maria E. Fernandez; Ella R. Garza; Jabria Pittman; Fernanda Velasco-Huerta; Tracy L. Judd; Jocelyn Hunyadi; Elvis Longanga Diese; Deevakar Rogith; William B. Perkison; Susan H. Fenton (BMC Health Services Research)
Abstract Background Remote patient monitoring (RPM) for hypertension management has become increasingly popular, demonstrating benefits for both clinics and patients. However, patient engagement in self-measured blood pressure (SMBP) monitoring remains low despite healthcare providers’ efforts. This study aimed to assess adherence and acceptance of RPM for SMBP among Texas Federally Qualified Health Center patients. Methods Participants enrolled in the SMBP monitoring program were recruited at three health centers. Data was collected from patient health records, and a questionnaire assessed hypertension self-management, technology acceptance, intentions, and attitudes toward SMBP. Thematic analysis was conducted for open-ended responses that followed each item, and multivariate linear regression assessed associations between psychosocial factors and SMBP use. Results The sample (n = 47) was 64% female, 89% Hispanic/Latino, and 75% uninsured. Participants used RPM for SMBP an average of 46 days and 72 times within the first 120 days (~ 4 months). Age and behavioral intention were significantly positively associated with more days of SMBP use. Three themes emerged from open-ended data: perceived ease of learning and using mobile patient portal for SMBP, perceived benefits of using mobile patient portal for SMBP, and intentions to continue using the mobile patient portal for SMBP. Conclusions Participants found RPM for SMBP acceptable and easy to use. Use varied over time, with intention to use RPM for SMBP and older age linked to more days of use. RPM can enhance patient experience by providing additional information to the provider, prompting self-management discussions, and empowering patients to better control their BP.